Strategi Israel Melawan Gerakan BDS - Muhamad Dzamirul Hakim; Wiwiek Rukmi Dwi Astuti (Jurnal ICMES, 2026)
This research discusses Israel's strategies to counter the narrative of the Boycott, Divestment, and Sanctions (BDS) movement between 2017 and 2019. Employing a descriptive qualitative method and drawing upon constructivism theory and the concept of narrative power, this study explores how Israel responded to the BDS narrative, which alleges human rights violations. The research highlights the implementation of anti-BDS laws within Israel, and intensive lobbying in the United States and the European Union, as well as efforts to deny entry and arrest BDS activists. The findings indicate that while Israel deployed various legal, diplomatic, and propaganda strategies to discredit the movement and associate it with antisemitism, these efforts faced significant challenges. Israel's repressive policies strengthened the BDS narrative regarding freedom of expression violations and the delegitimisation of Israel's democratic claims, fostering broader global solidarity and demonstrating the effectiveness of the BDS narrative in shaping international public opinion.